Space Vector Design Assisted Channel Modulation - Shuqing Lin; Yanfei Zhu; Zhi Yang (IEEE Access)
With the design idea of the index modulation (IM), media-based modulation (MBM) has been attracted a lot of attention due to that it not only offers optional transmission channels for physical security but also transmits additional channel index (CI) information for enhancing the spectral efficiency. In order to enhance the exploration of both the antenna index (AnI) information and the CI information, space vector design aided channel modulation (SVD-CM) is proposed. Firstly, the SVD Modulator is designed for extending the spatial index additional information by utilizing two types of pulse amplitude modulation (PAM) and secondary PAM constellations. In the SVD Modulator, it is divided into three parts, the Part-I of which is used to generate one spatial vector A with $N_{t}× 1$ dimensions, the Part-II, -III of which are jointly designed into two spatial vectors: B and C with $\frac {N_{t} }{2}× 1$ dimensions. Furthermore, aiming at carrying more CI information in the Channel Modulator, the spatial vector A is modulated by the specified CI vector with one part of CI bits into the quadrature component of the transmitted spatial MBM vector (TSMV). Two spatial vectors of B and C are modulated by two specified CI vectors with two other parts of CI bits into the in-phase component of the TSMV. Finally, the bit error probability of the SVD-CM is provided with the assumption of channel states information perfectly known at the receiver, and simulation results using the Monte Carlo method are presented to verify the advantage of the SVD-CM, in which the bit error rate (BER) performance achieved by the SVD-CM are better than the existing IM-, MBM-based schemes.